Amylin and Calcitonin: Potential Therapeutic Strategies to Reduce Body Weight and Liver Fat - Mathiesen, David S.; Lund, Asger; Vilsbøll, Tina; Knop, Filip K.; Bagger, Jonatan I. (Frontiers in Endocrinology, 2021)
The hormones amylin and calcitonin interact with receptors within the same family to exert their effects on the human organism. Calcitonin, derived from thyroid C cells, is known for its inhibitory effect on osteoclasts. Calcitonin of mammalian origin promotes insulin sensitivity, while the more potent calcitonin extracted from salmon additionally inhibits gastric emptying, promotes gallbladder relaxation, increases energy expenditure and induces satiety as well as weight loss. Amylin, derived from pancreatic beta cells, regulates plasma glucose by delaying gastric emptying after meal ingestion, and modulates glucagon secretion and central satiety signals in the brain. Thus, both hormones seem to have metabolic effects of relevance in the context of non-alcoholic fatty liver disease (NAFLD) and other metabolic diseases. In rats, studies with dual amylin and calcitonin receptor agonists have demonstrated robust body weight loss, improved glucose tolerance and a decreased deposition of fat in liver tissue beyond what is observed after a body weight loss. The translational aspects of these preclinical data currently remain unknown. Here, we describe the physiology, pathophysiology and pharmacological effects of amylin and calcitonin and review preclinical and clinical findings alluding to the future potential of amylin and calcitonin-based drugs for the treatment of obesity and NAFLD.